Sclerosing Encapsulating Peritonitis (SEP) due to Mycobacterium Bovis (Indian Journal of Case Reports, 2019)
Sclerosing Encapsulating Peritonitis (SEP), a visceral encapsulation syndrome of inflammatory origin either primary or secondary based on causation, is an infrequent cause of mechanical bowel obstruction that may commonly be seen in young patients. Preoperative diagnosis is quite challenging and usually missed due to the non-specific nature of the clinical picture. In most of the cases, a definitive diagnosis is reached intra and postoperatively with histopathological and culture findings. Herein, we report a young male patient that presented to our emergency department with signs and symptoms suggestive of intestinal obstruction. Intraoperatively, a thin membrane encasing the small bowels with transmesenteric herniation noted with a clinical diagnosis of SEP as the primary cause of obstruction. Postoperatively, a definitive cause was identified by histopathological findings and specimen culture. The report of this case, as one of the few male patients with this entity in the published literature, highlights the notion that surgeons should be vigilant to keep in mind this extremely rare cause while managing a patient with intestinal obstruction.